(untitled) (Revista de Psicología, 2025)
The Institute of Psychological Research (IIPsi) originated as a dual-affiliation Executive Unit (UE) following the approval of its creation by the board of the National Scientific and Technical Research Council (CONICET) on May 3, 2017 (Resolution No. 842/2017). Specifically, IIPsi is affiliated with both the National University of Córdoba (UNC) and CONICET, and is located within the Faculty of Psychology (UNC).